Impact of consumer ethnocentrism on China-Chic product consumption: a multigroup analysis of ethnic attributes - Cuixiang Tie; Yongkang Hou; Yueqiu Lei (Humanities & Social Sciences Communications)
Abstract The surge in China-Chic product (CCP) consumption poses a challenge for the localized marketing strategies of global brands. CCPs are fashionable products that incorporate traditional Chinese styles and modern design. The purpose of this research is to examine the factors that influence the purchasing behavior of CCPs among Chinese consumers, with a specific focus on the affective factor of consumer ethnocentrism (CE) and the rational factor of product evaluation, and to innovatively investigate the differences in CCP consumption between Han Chinese and ethnic minorities. A web-based study of 458 Chinese consumers revealed that CE was a relatively prominent determinant of CCP consumption compared with product evaluations across all ethnic consumer groups. Compared with that of ethnic minorities, when the evaluation of CCPs was greater, the likelihood that Han Chinese were willing to spend was greater, while it had no effect on ethnic minorities. Structural equation modeling analysis also suggested that patriotism and ethnic identity have a significant positive effect on enhancing CE, but consumers’ high culture confidence unexpectedly diminishes this tendency. These findings indicate that marketing in China that appeals to affective sentiments is feasible, but strategies that target Han Chinese need to emphasize product quality, whereas those directed at minority ethnic regions can cater to promotional activities and positioning strategies oriented toward subcultures to enhance ethnic identity.